Vascular Regulation of Developmental Neurogenesis - Vogenstahl, Johanna; Parrilla, Marta; Acker-Palmer, Amparo; Segarra, Marta (Frontiers in Cell and Developmental Biology, 2022)
Evolutionary studies indicate that the nervous system evolved prior to the vascular system, but the increasing complexity of organisms prompted the vascular system to emerge in order to meet the growing demand for oxygen and nutrient supply. In recent years, it has become apparent that the symbiotic communication between the nervous and the vascular systems goes beyond the exclusive covering of the demands on nutrients and oxygen carried by blood vessels. Indeed, this active interplay between both systems is crucial during the development of the central nervous system (CNS). Several neural-derived signals that initiate and regulate the vascularization of the CNS have been described, however less is known about the vascular signals that orchestrate the development of the CNS cytoarchitecture. Here, we focus on reviewing the effects of blood vessels in the process of neurogenesis during CNS development in vertebrates. In mammals, we describe the spatiotemporal features of vascular-driven neurogenesis in two brain regions that exhibit different neurogenic complexity in their germinal zone, the hindbrain and the forebrain.